Identification and characterisation of specific allergens of Abalone (haliotis midae; mollusca) and other seafood species - Lopata, Andreas L (Division of Immunology, 2018)
Shellfish and fish are sources of potent allergens in sensitised individuals. In view of the limited information available from published studies, especially on mollusc allergens, more detailed characterisation of the major allergens from different shellfish and fish is necessary to accurately predict cross-allergenicity. The need for a detailed characterisation of the immune response and the allergens in an indigenous mollusc species, followed a recent increase in patients presenting in the Cape Town area, with TY.pe I allergic reactions after ingestion of abalone (Haliotis midae). The first objective of this study was to determine the frequency and spectrum of reported hypersensitivity to abalone and other related seafood species in the Western Cape of South Africa. 105 volunteer subjects with suspected seafood allergy were recruited by means of a detailed seafood allergy questionnaire, advertised in the local press. The analysis of the questionnaire demonstrated clearly the importance of abalone, which was the third most frequently reported species (35%), after rock lobster and shrimp, of the 26 seafood species implicated in allergic reactions. Allergy to seafood was confirmed by the presence of specific IgE using in-house and commercial radioimmunoassays (RASTs). A novel Abalone-RAST identified specific IgE to abalone in 17/38 subjects who reported adverse reaction following the ingestion of abalone. The novel Abalone-RAST correlated positively not only with the phylogenetic closely related Snail-RAST (p<0.01) but also with squid and several indigenous crustacean species. Among subjects with multiple seafood allergies, the immune responses to molluscs species were found to be diverse. The presence of species specific allergens in the mollusc group was supported by the very low frequency of concurrent sensitivity to all mollusc species (13%) compared to concurrent sensitivity between mollusc and among the crustacea and fish group (42% and 56% respectively). The persistence of specific IgE, following a period of more than three years of seafood avoidance, was demonstrated in the mollusc species studied. The second objective was to investigate the specific immune responses to local seafood in more detail using RAST-inhibition experiments, skin prick tests (SPTs) and Western blots to demonstrate the presence of species-specific allergens. Sensitivity for the detection of abalone allergy was improved using an additional in-house SPT in six RAST negative subjects (23/38, 61 %). RAST-inhibition experiments with abalone extract demonstrated the highest degree of cross-reactivity with the Snail-RAST. In addition, a strong inhibition was achieved using commercial crustacean RASTs, confirming the presence of cross-reacting allergens in species of the same and other seafood groups. However, the low inhibitions achieved with the indigenous black mussel and squid extracts indicated that their allergen compositions differ from the species utilised in the commercial RASTs. Unique species-specific protein bands could be detected by SDS-gel electrophoresis, which clearly distinguished related mollusc species. These have not been demonstrated previously. Western blot analysis of different mollusc species identified several prominent allergens. An unexpected finding was the appearance of novel specific IgE binding reactivity after cooking the abalone. Several IgE binding proteins with similar molecular weights could be detected in immuno blots of indigenous crustacean and fish species. The next objective was to characterise the hypersensitive reactions to the local abalone species (H midae) in detail and identify the allergens found in this mollusc species. The questionnaire on abalone sensitive subjects revealed that asthma-like symptoms and the delayed onset of symptoms were frequent in sensitised individuals (42% and 34% respectively). This has previously only been reported for snail and in one case report on abalone. Surprisingly, the five abalone sensitive subjects who were studied in more detail had concurrent sensitivity to HDM and, analysed by RAST-inhibition, demonstrated two distinct types of responses. One set of subjects demonstrated a strong inhibition by HDM, indicating clearly for the first time that cross-reacting allergens or epitopes must exist between the food allergens from abalone and the air borne allergens found in HDM. SDS-gel electrophoresis demonstrated common but in addition species-specific protein bands even between very closely related abalone species from South Africa, Australia and Japan. Western blot analysis revealed two major allergens with molecular weights of about 38 and 45 kDa. Their remarkable thermal stability was demonstrated by various in-vitro and in-vivo assays. These two allergens were also present in extracts of other indigenous mollusc species, and surprisingly in some local crustacean and fish species. The individual immune responses to mollusc species were very heterogeneous for each analysed individual. The 38 kDa allergen is believed to belong to the protein family of tropomyosins, as was supported by specific IgE binding to recombinant tropomyosin of shrimp. This novel 45 kDa allergen of the South African abalone (H midae), was registered with the WHO International Union of Immunological Societies (IUIS) as Hal m 1. It is only the second allergen recognised for a mollusc species after Tod p 1 from squid. A further aim of these studies was to generate monoclonal antibodies (MoAbs) to the mollusc allergens using the hybridoma technology. The MoAbs were used, due to their consistent specific binding, to identify cross-reacting allergens among species of different seafood groups. In addition, I attempted to develop an immunologic test to distinguish between abalone species from different parts of the world. This test is of importance for the South African police to identify for forensic purposes unequivocally, fresh or processed abalone tissue exported illegally from South Africa to the Far East. Three ELISA- and Western blot assay positive clones were analysed. They demonstrated highly individual binding profiles when binding to fresh and cooked mollusc species was analysed. MoAb clones 2.11 and 2.12 (generated to the same protein of abalone) lacked complete binding to four and two of the ten abalone species respectively, allowing for very distinct species identification. Furthermore, antibody binding to cross-reacting proteins in crustacea and fish was also detected. Western blot results demonstrated clearly that these two antibodies bind to different epitopes on the same protein, making them very useful as tool for allergen and species identification. Finally, an amino acid analysis of the 3 purified antibody binding fractions of abalone was conducted. These proteins were rich in glutamine and asparagine, like tropomyosin, but differed significantly from tropomyosin with respect to serine content. The immunological findings using different patient specific sera and the monoclonal antibodies generated, provide important new information and insights into the concordant and multiple positive sensitivity to molluscs, crustacea and fish, and new information about the complexity and stability of immune responses to seafood and mollusc allergens observed in allergic subjects.